Hubungan Kemampuan Membaca Pemahaman dengan Keterampilan Menulis Paragraf Deduktif siswa kelas XI SMA Negeri I Dua Koto Kabupaten Pasman - Yudersam, Yeli; Chan, Wirsal; DN, Upit Yulianti (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by the first, low motivation of students in reading comprehension because reading materials available bit. Second , the method used is less interesting and less varied. Third, the lack of student interest in learning writing skills especially writing paragraphs deductive. Fourth, the lack of students skills in reading comprehension and deductive writing paragraphs. This study aims to determine the relationship kamampuan reading comprehension with writing paragraphs deductive skills class XI SMA Negeri I Pasaman Two Koto. This research is quantitative research using descriptive methods , Arikunto ( 2002:10 ). The population in this study were students of class XI SMA Negeri I Two Koto Pasaman totaling 190 people. Proportional random sampling technique sampling , sample numbered as many as 40 people. Analysis using the formula korelasi.Berdasarkan outcomes research is that, first reading comprehension ability of students are on qualification